Descending necrotizing mediastinitis secondary to a dental infection - Edson Martins de Oliveira Junior; Raphael Teixeira Moreira; Tayguara Cerqueira Cavalcante (University of São Paulo, 2012)
Descending necrotizing mediastinitis is a rare type of deep infection of the soft tissues of the face, originating from cervical and oral infections, typically dental infections. It is associated with high mortality, due to its high invasive potential and the fact that the diagnosis is often delayed. We report the case of a 42-year-old female patient presenting with severe trismus, fever, purulent intraoral drainage, dysphagia, and dysphonia, accompanied by edema and redness in the cervical region. She was diagnosed with necrotizing descending mediastinitis secondary to a dental infection after the extraction of a mandibular third molar. The patient underwent surgical drainage and intravenous antibiotic therapy. Despite the development of septicemia, the evolution was favorable and the patient was discharged on post-admission day 20. Early and accurate diagnosis, together with prompt treatment, is imperative for better outcomes in this rare condition.